In severe acne vulgaris, TNF‐α gene variants are connected to increased TNF‐α gene expression and insulin resistance - AbdElneam, Ahmed Ibrahim; Alhajlah, Sharif; Al‐Dhubaibi, Mohammed Saleh; Bahaj, Saleh Salem; Mohammed, Ghada Farouk; Alantry, Ahmed Kaid; Atef, Lina Mohammed (Skin research and technology, 2024)
Background Acne vulgaris (AV) is a chronic inflammatory skin condition affecting the pilosebaceous unit, commonly presenting as comedones, papules, pustules, or nodules on the face, upper limbs, torso, and back, with comedones formation being the primary pathology leading to disfiguring inflammation, hyperpigmentation, scarring, and psychological impact. Aim The purpose of this study was to investigate the significance of two genetic variants in the promoter region of the tumor necrosis factor‐alpha (TNF‐α) gene and their association with insulin resistance (IR) in acne patients. To understand how these variants contribute to AV and its associated IR. Subjects and methods An analytical cross‐sectional study with a case‐control design and research evaluation was carried out on 87 AV patients and 73 healthy volunteers. The medical histories of both groups were obtained, as well as the severity and duration of inflammation among acne sufferers, as well as demographic data. Biochemical analysis was performed on both sets of participants, including fasting blood glucose levels, insulin levels while fasting, IR, and serum TNF‐α. PCR‐RFLP analysis identified −863 G > A (rs1800630) and −308 G > A (rs1800629) variations, and real‐time PCR analysis evaluated TNF‐α gene expression in both patients and healthy people. Results Acne patients exhibited significantly higher levels of IR, fasting glucose, fasting insulin, serum TNF‐α, and TNF‐α folding change, when compared to healthy controls. The co‐dominant model for −863 G > A and −308 G > A variants exhibited significant variations between the two groups. Severe acne patients who had the A/A genotype for −308 variants exhibited higher levels of IR, serum TNF‐α, and TNF‐α folding change. Highly significant positive linear correlation between IR, serum TNF‐α, and TNF‐α folding change in severe AV. Conclusion There is a correlation between AV, especially severe acne, and the −863 G > A and −308 G > A polymorphism, which influences TNF‐α gene expression and serum TNF‐α levels.